Indirect terrestrial transmission of amphibian chytrid fungus from reservoir to susceptible host species leads to fatal chytridiomycosis. (29th December 2020) - Burns, Thomas J.; Scheele, Ben C.; Brannelly, Laura A.; Clemann, Nick; Gilbert, Deon; Driscoll, Don A.
Abstract: The amphibian chytrid fungal pathogen ( Batrachochytrium dendrobatidis, henceforth Bd ) has had a devastating impact on biodiversity, causing the decline or extinction of over 500 amphibian species. Yet, our understanding of Bd transmission pathways remains incomplete, in particular for host species with weak aquatic associations, and between reservoir and susceptible host species. We examined Bd transmission from a potential reservoir host to a potentially susceptible critically endangered host; directly assessing the capacity of the former to transmit Bd, and the susceptibility of the latter as a Bd host. Using cohousing versus sequential use of the same enclosure by the two species, we distinguished the effects of direct versus indirect (environmental) transmission. Our study provides clear evidence that both direct and indirect terrestrial transmission from a reservoir to susceptible host species results in fatal chytridiomycosis. Transmission mode had no effect on overall morbidity or disease progression in the susceptible species. Our results demonstrate that reservoir and susceptible hosts do not need to be in the same place at the same time, or within an aquatic environment for transmission to occur. Our demonstration of indirect terrestrial transmission from a reservoir to susceptible host identifies mechanisms by which Bd may drive ongoing declines in populations where the pathogen is now endemic. Identifying these transmission pathways is important for understanding long‐term extinction vulnerability of remnant populations of declining species challenged by disease. Abstract : Amphibian chytrid fungus ( Batrachochytrium dendrobatidis, Bd ) has had a devastating impact on biodiversity. Yet, our understanding of Bd transmission pathways remains incomplete, especially for species with weak aquatic associations, and between reservoir and susceptible host species. We examined Bd transmission from a reservoir host to a potentially susceptible critically endangered host, by directly assessing the capacity of the former to transmit Bd and the susceptibility of the latter as a Bd host. Using cohousing versus sequential use of the same enclosure by the two species, we distinguished the effects of direct versus environmental transmission. Our results demonstrate that reservoir and susceptible hosts need not be in the same place at the same time, or within an aquatic environment, for transmission to occur. Our demonstration of indirect terrestrial transmission from a reservoir to susceptible host identifies mechanisms by which Bd may drive ongoing declines in systems where it is now endemic. Photo credit: Damian Goodall, Zoos Victoria